Let the convicts speak: a critical conversation of the ongoing language debate in convict criminology - Ortiz, Jennifer M. (Criminal justice studies, 2022)
In 2020, some scholars publicly demanded that the newly established Division of Convict Criminology (DCC) of the American Society of Criminology (ASC) change its name. Critics asserted that the use of ‘convict’ caused further stigmatization of those of us with direct criminal justice experience. Unbeknownst to those critics, prior to the official formation of the DCC, the informal group known as Convict Criminology engaged in a decades long conversation about language and appropriate terminology. This paper responds to the critiques by exploring the power of language, summarizing various sides of the ongoing language debate, reviewing existing convict criminology research, and addressing structural violence within the academy. We conclude with a call to action that asks scholars to address the endemic structural violence in academia that perpetuates our oppression before attempting to police our language.